Reconhecimentos hidrográficos na cartografia portuguesa da costa centro e sul de Moçambique no século XIX - Roque, Ana Cristina; Ferrão, Lívia (Africana Studia, 2020)
Through the analysis of a map collection made by the members of the Cartography Commission that can be found in the archives of the CEHCA, we intend to present a synthesis of the hydrographical reconnaissance operations undertaken by this Commission, in the central and southern areas of Mozambique, in the 19th century. We wish to emphasize its historical importance for this region and particularly for an evaluation of the evolution and changes of certain aspects in the Mozambican coast. These maps enclose important information and contribute today for a better knowledge of these areas.